An Orbital Free Ab-initio Molecular Dynamics Study of Liquid Pt for Static and Dynamic Properties (Dhaka University Journal of Science, 2022)
Using the orbital free ab-initio molecular dynamics (OF-AIMD) simulation scheme we have examined the static and dynamic properties of liquid Pt at the thermodynamic state near to its melting point. In this simulation scheme, the Hohenberg and Kohn orbital free density functional theory (OF-DFT) has been employed. In OF-DFT, we have estimated the electron-ion interaction by a local pseudopotential and also controlled the exchange-correlation energy functional by using the local density approximation (LDA). The static properties, for instance, static structure factor, S(q), pair correlation function, g(r), coordination number, Nc, and isothermal compressibility, κT, are examined. Using the familiar single-particle dynamics, the self-diffusion coefficient and self-intermediate scattering function are studied. It is found that the self-intermediate scattering function is controlled by the selfdiffusion coefficient. While for studying the collective dynamics of the system, we have calculated velocity of sound from the longitudinal dispersion relation and shear viscosity from the transverse current correlation function, JT(q, t). The OF-AIMD results are nicely fit with the theoretical and experimental results accessible to us for comparison.Dhaka Univ. J. Sci. 69(3): 179-185, 2022 (June)